수중 박테리아 제거를 위한 상업용 여재의 특성 비교 - 김문주; 박성직 (한국수처리학회지, 26(1), 2018)
In this study, we investigated the characteristics of bacteria removal by commercial filter media including sand, birm, garnet, feroxer, and hydro-filt. Escherichia coli ATCC 11105 was used as model bacteria and a polyethylene column with a length of 150 mm and an inner diameter of 16 mm. Bacteria solution was injected to the column downward at a flow rate of 0.7 mL/min. Column experiments were performed under different pH (4-8) and ionic strength (0-80 mM), and removal percentage and sticking efficiency were quantified from the breakthrough curves obtained from the column experiments. As the pH was increased, both removal percentage and sticking efficiency were decreased. Bacterial attachment onto sand, birm, garnet, feroxer, and hydro-filt were increased with increasing ionic strength from 0 to 20 mM but decreased with increasing ionic strength above 20 mM. The bacterial removal percentage was the highest in sand, but the attachment efficiency was highest in garnet under pH experiment. The bacteria removal percentage and sticking efficiency under different ionic strength were highest in sand. Sticking efficiency is considered as an appropriate parameter to evaluate the efficiency of filter media for the removal of bacteria under different size of filter media and solution chemistry. KCI Citation Count: 1